2014
DOI: 10.1002/jgm.2762
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing cationic and neutral lipids for efficient gene delivery at high serum content

Abstract: Background Cationic liposome (CL)-DNA complexes are promising gene delivery vectors with potential applications in gene therapy. A key challenge in creating CL-DNA complexes for applications is that their transfection efficiency (TE) is adversely affected by serum. In particular, little is known about the effects of high serum contents on TE even though this may provide design guidelines for applications in vivo. Methods We prepared CL-DNA complexes in which we varied the neutral lipid (DOPC, glycerol-monool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 69 publications
0
48
0
Order By: Relevance
“…29-33,58-62 Fig. 3a shows transfection efficiency (TE; a measure of expression of an exogenous gene that is transferred into the cell by the lipid carrier) as a function of mol% cationic lipid for complexes transfecting mouse fibroblast cells at various MVL/DOPC ratios with the headgroup charge of the MVLs varied between +2 e and +5 e .…”
Section: Transfection Efficiency Of Distinct Phases Of Cationic Liposmentioning
confidence: 99%
“…29-33,58-62 Fig. 3a shows transfection efficiency (TE; a measure of expression of an exogenous gene that is transferred into the cell by the lipid carrier) as a function of mol% cationic lipid for complexes transfecting mouse fibroblast cells at various MVL/DOPC ratios with the headgroup charge of the MVLs varied between +2 e and +5 e .…”
Section: Transfection Efficiency Of Distinct Phases Of Cationic Liposmentioning
confidence: 99%
“…As commonly reported for lipoplexes, serum, which is a substantial barrier for gene delivery in vivo [57,58] decreased the overall level of transgene expression in our studies as well. However, compared to DOPE-and cholesterol-based lipoplexes under the same experimental condition (either with or without serum), the TACH lipoplexes consistently mediated higher gene transfection, suggesting that TACH lipoplexes would serve as an improved gene delivery system in both cultured cells and in animals/humans.…”
Section: Luciferase Gene Transfection By Lipoplexes Comprising Tach-bmentioning
confidence: 49%
“…(ii) multivalent cationic lipids [67,78,139,178,181], derivated oligoamines [182] and tripeptide multivalent lipids [122]; (iii) cationic polymers derivatives from PEI [124,127,183,184], PAMAM [132,140], PDMAEMA [123,133,185], PAA [103,131,186,187], chitosan [188], polyphosphoramidates [189], polyhydroxyalkanoate [92], polyamines [107], polyaminoacids [127,190] or diblock copolymers [191]; (iv) polycations from calixarene [40,136,165,192] or cyclodextrin [134,135,142,164,193] derivatives; (v) lipopolymers from lysine derivatives [170]; (vi) pendant polymercationic cyclodextrins [129,130,163]; and (vii) cationic polymer-cyclodextrin polyrotaxanes [89]. The picture that results from these transfection studies is that many of the polyplexes show efficacies comparable to that reported by the Lipo2000 positive control and also by most of the commercial or synthezised univalent CLs, but its efficacy as transfecting agents of DNA is still below than that reported by most of t...…”
Section: Biochemistry Characterizationmentioning
confidence: 99%
“…The results confirm that all these optimized formulations did not report any toxicity to the cell lines studied, the cell viability after transfection being considerably better than the commercial control Lipo2000. The cell viability/cytotoxicity of several complexes between nucleic acids and a wide variety of recent synthesized MVCVs has been analyzed: (i) GCLs as cholesterol-based with alkyl or oligo-oxyethylene spacers [118,119,121,206,207], aromatic-based with alkyl or oligo-oxyethylene spacers [46], ammonium derivatives [54,71,93] imidazolium derivatives [45,75,99] and pyridinium derivatives [57] with alkyl type spacers, aminoacid-based [64,208], SS14 linkers [66], gemini-like amphiphilic peptides [150] or cyclen-based CLs [120,180]; (ii) several MVCLs [67,72,122,181,182]; (iii) cationic polymer-derivatives from PEI [124,127,183,209], PAMAM [140], PDMAEMA [123,133], chitosan [188], polyphosphoramidates [189], polyhydroxyalkanoates [92], polyamines [107,187] or polyaminoacids [127,190]; (iv)…”
Section: Accepted Manuscriptmentioning
confidence: 99%